Autism in Aotearoa: Is the RAADS-14 a valid tool for a New Zealand population? - Kember S; Williams MN (Hogrefe for the European Association of Psychological Assessment (EAPA))
Screening measures for autism spectrum disorder (ASD) are important tools for clinicians and researchers. However, where a measure developed and validated for one population is used with another, its performance in this new context must be carefully examined. The RAADS-14, a brief ASD screen developed in Sweden, was evaluated with a sample of New Zealand adults (N = 387), 41 of whom self-reported a prior diagnosis of ASD. The convergent validity of the RAADS-14 (Hypothesis 2) was supported by a strong positive correlation with the AQ-10 (short version of the Autism Spectrum Quotient), r = .81. Discriminant validity (Hypothesis 3) was also supported by a strong negative correlation with the EQ-Short (short version of the Empathy Quotient), r = −.75. However, the measure did not meet inferential criteria for internal consistency (Hypothesis 1), and confirmatory factor analysis (CFA) found a poor fit of the proposed three-factor model (Hypothesis 4) to the data. A cut-off score of 14/42 provided adequate sensitivity (95%) to detect participants with self-reported ASD diagnoses, but not adequate specificity (70%), suggesting a very high rate of false positives should be expected if relying on RAADS-14 scores alone to interpret presence of ASD. In sum, our results do not provide sufficient evidence of reliability and validity to support the use of the RAADS-14 with the New Zealand population. We provide suggestions for refinement of the RAADS-14 that may lead to increased reliability and validity.
This version of the article may not completely replicate the final authoritative version published in European Journal of Psychological Assessment at https://doi.org/10.1027/1015-5759/a000598. It is not the version of record and is therefore not suitable for citation. Please do not copy or cite without the permission of the author(s).
Keywords: autism spectrum disorder; ASD; RAADS-14; screening; validity; 1701 Psychology